2011
DOI: 10.2174/156800911796191024
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells: General Characteristics and Relevance to Clinical Management of Pancreatic Cancer

Abstract: Recent studies describe a heterogeneous population of cells of the myeloid lineage, termed myeloid derived suppressor cells (MDSC), which are observed with increased prevalence in the peripheral blood and tumor microenvironment of cancer patients, including pancreatic cancer. Accumulation of MDSC in the peripheral circulation has been related to extent of disease, and correlates with stage. MDSC have primarily been implicated in promoting tumor growth by suppressing antitumor immunity. There is also compelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 176 publications
(277 reference statements)
1
64
0
Order By: Relevance
“…Inhibiting MDSCs in patients with pancreatic adenocarcinoma may reverse immune suppression [30]. It has recently been shown that soluble factors contribute to the up-regulation of murine MDSCs in the murine mode and immune dysfunction of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting MDSCs in patients with pancreatic adenocarcinoma may reverse immune suppression [30]. It has recently been shown that soluble factors contribute to the up-regulation of murine MDSCs in the murine mode and immune dysfunction of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of IL-17 and Th17 cells has been confirmed in almost all types of invasive cancers, and IL-17 signaling activation related to cell proliferation, tumor growth and progression, and treatment resistance has been shown 7) . Suppressive myeloid cells were previously described in patients with cancer 8,9) , although the functional significance of these cells in the immune system has only recently been evaluated. Accumulating evidence [10][11][12][13] suggests that a population of cells with suppressive activity, referred to as MDSCs, may contribute to the negative regulation of immune responses during cancer and other conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The MDSC population has been shown to increase in cancer patients343536. Relatedly, granulocyte colony-stimulating factor (G-CSF) was shown to be one of the key cytokines secreted by tumor cells to mediate MDSC production27.…”
Section: Resultsmentioning
confidence: 99%